Kajian Struktur Ekonomi dan Sektor Unggulan Di Kabupaten Lebong - Yuningsih, Windi Tetra; Sumantri, Bambang (Convergence: The Journal of Economic Development, 2023)
This study aims to examine the economic structure and leading sectors in Lebong Regency with analytical tools in the form of economic structure analysis, LQ, DLQ, Shift-Share, and Overlay. The data used is in the form of secondary data obtained from the Central Bureau of Statistics in the form of Gross Regional Domestic Product (GRDP) data from 2017 to 2021. The results of the economic structure analysis show that the highest GRDP contribution comes from the Agriculture, Forestry and Fisheries sectors. The Electricity and Gas Procurement Sector provides the lowest GRDP contribution of all existing sectors. Lebong Regency has leading sectors including the construction sector; wholesale and retail trade, car and motorcycle repair; sector of Provision of Accommodation and Food and Drink; Government Administration, Defense and Compulsory Social Security sectors; as well as the Other Services sector.   Keywords :  Leading Sector1, LQ2, DLQ3, Shift-share 4